If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10 + -4(3x + 2y) = 0 10 + (3x * -4 + 2y * -4) = 0 10 + (-12x + -8y) = 0 Solving 10 + -12x + -8y = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-10' to each side of the equation. 10 + -12x + -10 + -8y = 0 + -10 Reorder the terms: 10 + -10 + -12x + -8y = 0 + -10 Combine like terms: 10 + -10 = 0 0 + -12x + -8y = 0 + -10 -12x + -8y = 0 + -10 Combine like terms: 0 + -10 = -10 -12x + -8y = -10 Add '8y' to each side of the equation. -12x + -8y + 8y = -10 + 8y Combine like terms: -8y + 8y = 0 -12x + 0 = -10 + 8y -12x = -10 + 8y Divide each side by '-12'. x = 0.8333333333 + -0.6666666667y Simplifying x = 0.8333333333 + -0.6666666667y
| -5x-20-7x=-68 | | -3(5y+6)-3(y-8)= | | -14=-8+2w | | 3(3r+3)-2(r-1)= | | 7b=4(b+30) | | 2ln(2x)=6 | | -2(3y-1)-2(y-6)= | | (x^2-2x+4)(x^2+3x-11)=0 | | x-13=19+3x | | 4(g+8)=7+4g | | 2(8q-5)=4q | | (m^2+m-6)/(m+4) | | 29-10= | | 3c+1=c+1 | | 2k-3(2k-3)=45 | | 5=7w+8w+2 | | 60=-12r | | -9(b-4)-1= | | X=842-13 | | k/17=-7/17 | | (3x+14)/5=8-2x | | 4x+2+3x-8=8 | | a-19=-25 | | 2x-y+150=180 | | z+4=12 | | 1(2/3)+(9/5) | | X+199=99 | | 45/0.15 | | 10/400 | | 10/40 | | -3[4-(3b+3)]=4-3(3b+5) | | (x/7)=(12/4) |